The Effects of Peace Education Program on University Students: Case Study of University of Zakho, Kurdistan Region, Iraq - Nizar Ismat Ali; Diman Zuhair Sami Jacksi; Mohammed Ismael Sulaiman; Ali Saeed Saleem (STAI Publisistik Thawalib Jakarta, 2025)
Peace education globally equips students with skills for harmony and conflict prevention using innovative methods, technology, and community initiatives, fostering intercultural understanding and sustainable peace. This study aims to evaluate HWPL’s peace education program’s impact on intercultural sensitivity, student attitudes, behaviours, and its implications for Iraqi university curricula. This study employed a mixed-methods approach, combining qualitative and quantitative research to assess the impact of HWPL’s 12 peace education lessons. The research spanned one semester (15 weeks) during the 2023–2024 academic year, with data analysed using SPSS. The study’s findings revealed a statistically significant difference between pre-test and post-test results, favouring the post-test, indicating improved student understanding of peace education. The mean scores of the 12 lessons ranged from 1.93 to 2.26, with lesson 2, focused on appreciating diverse viewpoints, traditions, races, and affiliations to promote societal harmony, ranking highest at 2.26. The results positively impacted university students’ perspectives towards peace education. Additionally, no statistically significant gender differences were found in average peace education scores. The researchers concluded with several recommendations and suggestions for future studies to explore this field further. Conclusion: The study showed that peace education significantly improved students’ understanding of peace and diversity, supporting its expansion in universities, schools, and international collaborations.